Intertextualidade e identidade social: a construção de um papel para os militares em textos da imprensa - Martins, André R. N. (Cadernos de Linguagem e Sociedade, 2010)
This paper analyses the discursive process of the press based on a social view of literacy. It attempts to show how the institution of the press constructs social roles and how a particular form of intertextuality is set to work. The texts which are analysed come from the MA thesis O discurso da imprensa sobre os militares (The discourse of the press about the Armed Forces, 1992). Five texts are analysed focussing on the category of intertextuality, on the immediate social context and on the context of culture. The paper tries to identify the social role of the Armed Forces in Brazil and how such a role is contructed by the press.